Implementación de un sistema cliente - servidor utilizando la metodología xp (programación extrema) para la automatización de la información de los servicios hospitalarios del patronato de amparo social del GAD municipal del cantón La Maná - Quishpe Morocho, Jenny Yajaira (2015)
The advancement of technology has evolved in an accelerated manner and has become necessary tools to improve information management, generating new ideas to provide solutions to big needs facing today. With the "Implementation of a client - server system, using the methodology XP (extreme programming), for the automation of hospital information and services of GAD Municipal Social Ampere of La Maná" can determined that the results obtained are satisfactory because we can have a fast, efficient and timely to patients who daily make use of medical services provided by the institution, because the system was developed using the XP methodology (extreme programming)....